Pioneers and progress: white Rhodesian nation-building c.1964-1979 - Kenrick, D (2016)
The thesis explores the white Rhodesian nationalist project led by the Rhodesian Front (RF) government in the UDI-period of 1965 to 1979. It seeks to examine the character and content of RF nation-building, arguing that it is important to consider the context of wider global and regional trends of nationalism at the time. Thus, it places the white Rhodesia within wider ‘British World’ studies of settler societies within the British Empire, but also compares it to other African nationalist movements in the 1960s and 1970s. It studies white Rhodesian nationalism on its own terms as a sincere, albeit unrealistic, alternative to majority-rule independence, and considers how the RF adapted over the period in its continuing attempts to justify minority-rule in an era of global decolonisation. Two thematic sections examine the RF’s nation-building project in systematic detail. The first section, on symbolism, considers Rhodesia’s processes of ‘symbolic decolonisation’. This involved white Rhodesians creating new national symbols not associated with Britain or the British Empire. Processes by which new national symbols were chosen are used as a lens to explore white Rhodesian debates about their ‘new’ nation after the Unilateral Declaration of Independence (UDI) was taken in 1965. They reveal the ambiguities and complexities at the heart of the RF’s nation-building project; a project that was frequently exclusionary and hotly contested at every opportunity. The second section explores how history was used to help create and defend the nation, adding to studies of the use of history in nationalist projects. It considers a range of non-professional sites of history-making, demonstrating the complicated relationships between these different sites and the state’s wider nationalist agenda. It also explores how history was invoked to justify and defend minority-rule independence both before and after UDI.